DEVELOPMENT OF PRODUCTION TECHNOLOGIES OF LEAD PARTS AND SHEETS FOR RADIATION PROTECTION INSTRUMENTATION AND MEANS FROM RECYCLED PARTS - V. A. Pumpur; V. M. Ilyushenko; G. P. Korotkin (Литьë и металлургия)
Urgency of use of secondary lead materials and creation of appropriate technologies for production of lead parts and sheets for devices and means of radiation protection is briefly grounded. The methodology and the main results of investigations on development of technologies of production of lead parts and sheets for devices and means of radiation protection out of secondary raw materials are presented.